Catalyst-loaded electrode as well as preparation method and application thereof
By adding polymer adhesives to the electrolyte, the electrode of the load catalyst is prepated to use the electrical deposition method to solve the problem of low stability of the metal oxide catalyst, realize the high activity and high stability of the electrode, and it has a wide range of applications. potential.
Patent Information
- Application Number
- CN202310920310.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-01-28
AI Technical Summary
The metal oxide catalyst synthesized by existing electrochemical deposition methods is not stable, resulting in peeling off on the electrode surface, limiting its large-scale application.
By adding polymer adhesives to the electrolyte, the electrode of the load catalyst is prepared by the electrical deposition method, and the combination of catalysts and electrode matrix is more close to reduce the risk of falling off.
Improve the catalytic activity and stability of the electrode, simplify the preparation operation, reduce the requirements for device equipment, and have broad market application prospects.
Smart Images

Figure CN119372695A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of electrode material preparation and electrocatalysis technology, and in particular, to a catalyst-loaded electrode and a preparation method and application thereof. Background Art
[0002] Ammonia (NH3) is an important chemical that can be used as fertilizer, fuel or chemical raw material, and plays a huge role in agriculture, medicine, chemical industry and other industries. In industry, ammonia is mainly prepared by the Haber-Bosch method, using hydrogen and nitrogen as raw materials through a high temperature and high pressure process. However, this method has high energy consumption, dangerous reactants, and the greenhouse gases emitted are not conducive to the environment. Therefore, it is urgent to develop a cleaner and more efficient alternative method. At the same time, with the development of industrialization, a large amount of nitrate is discharged into the environment, causing environmental pollution, destroying the natural nitrogen cycle, and posing a serious threat to animals and plants.
[0003] At present, by applying a certain voltage to the reaction electrode by electrochemical methods, nitrate can be reduced to generate ammonia on the cathode surface, wherein the electric energy required for the reaction can be converted from renewable energy sources such as wind energy, solar energy and tidal energy. Compared with the traditional Haber-Bosch method, the electrocatalytic method has a good application prospect in the degradation of nitrate waste due to its mild reaction conditions, environmental friendliness, high efficiency and excellent economy. Therefore, it is of great research value to prepare a catalyst electrode for the electroreduction of nitrate to synthesize ammonia with high activity, high stability and high efficiency.
[0004] In recent years, a large number of studies have been devoted to the development of transition metal oxide catalysts. Among them, spinel oxides provide great possibilities for electrochemical degradation of nitrates due to their flexible ion arrangement, multivalent structure and high electronic conductivity. Compared with the traditional hydrothermal synthesis method, the catalyst synthesized by electrochemical deposition has the advantages of controllable thickness, low cost and high efficiency. However, the metal oxide catalyst precursor synthesized by electrochemical deposition usually has a loose structure and is easy to peel off from the electrode surface after calcination. The obtained catalyst is not stable, which greatly limits its large-scale application. Summary of the invention
[0005] The purpose of the present invention is to provide a catalyst-loaded electrode and a preparation method and application thereof, so as to improve the catalytic stability and activity of the electrode.
[0006] In order to achieve the above object, the present disclosure provides a method for preparing a catalyst-loaded electrode in a first aspect, the method comprising the following steps:
[0007] Obtaining an electrolyte containing metal ions, wherein the electrolyte further contains a polymer binder, and the weight ratio of the metal ions to the polymer binder is (0.05-0.5):1;
[0008] Placing the working electrode in the electrolyte to perform an electrodeposition reaction to obtain a working electrode after the reaction;
[0009] The working electrode after the reaction is dried and calcined to obtain a catalyst-loaded electrode.
[0010] Optionally, the metal ion is at least one selected from cobalt ion, nickel ion, iron ion, copper ion and manganese ion;
[0011] Preferably, the metal ions are cobalt ions and nickel ions, wherein the molar ratio of the cobalt ions to the nickel ions is (1-3):1.
[0012] Optionally, the polymer binder is at least one selected from quaternary ammonium salt polymers, quaternary phosphate salt polymers and quaternary sulfide salt polymers;
[0013] Preferably, the polymer binder is at least one selected from polymethacryloyloxyethyltrimethylammonium chloride, polydimethyldiallylammonium chloride, quaternized polyvinylimidazole and polyacrylamidepropyltrimethylammonium chloride.
[0014] Optionally, in the electrolyte, the concentration of the metal ions is 10 to 100 mmol / L.
[0015] Optionally, the electrodeposition reaction includes a first reaction stage, a second reaction stage and a third reaction stage which are performed sequentially;
[0016] The conditions of the first reaction stage include: a current density of -1 mA / cm 2 To -1.5mA / cm 2 , time is 60~120s;
[0017] The conditions of the second reaction stage include: a current density of -0.2 mA / cm 2 To -0.5mA / cm 2 , time is 10 to 30 minutes;
[0018] The conditions of the third reaction stage include: a current density of -0.052 mA / cm 2 To -0.1mA / cm 2 , time is 60 to 90 minutes.
[0019] Optionally, the electrodeposition reaction is carried out using a three-electrode system, wherein the three-electrode system includes a reference electrode, a counter electrode and the working electrode;
[0020] The working electrode is at least one selected from a nickel foam electrode, a carbon electrode, a metal platinum electrode and a carbon paper electrode;
[0021] The reference electrode is a silver / silver chloride electrode and / or a saturated calomel electrode;
[0022] The counter electrode is a platinum sheet electrode and / or a carbon rod electrode.
[0023] Optionally, the drying conditions include: a temperature of 80 to 100° C. and a time of 12 to 24 hours.
[0024] Optionally, the calcination conditions include: the calcination atmosphere is an inert gas, the temperature is 200 to 400° C., and the time is 1.5 to 3 hours.
[0025] In a second aspect of the present disclosure, there is provided a catalyst-loaded electrode prepared by the method described in the first aspect of the present disclosure.
[0026] In a third aspect of the present disclosure, there is provided a use of the catalyst-loaded electrode described in the second aspect of the present disclosure in electrocatalytic production of ammonia.
[0027] Through the above technical scheme, the present invention adds a polymer binder to the electrolyte and adopts the electrodeposition method to prepare the catalyst-loaded electrode. The catalyst is more tightly combined with the electrode matrix and is not easy to fall off. The catalytic activity and stability are high, and the preparation operation is simple, and the requirements for equipment are low, which has broad market application prospects. The catalyst-loaded electrode is applied to the electrocatalytic nitrate reduction ammonia synthesis reaction, which opens a way for the design and preparation of nitrate reduction ammonia catalyst in the future, and has great application value in wastewater treatment, ammonia industrial product synthesis, etc.
[0028] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:
[0030] Figure 1 This is the XRD pattern of the catalyst-loaded electrode prepared in Example 1.
[0031] Figure 2 This is the XPS graph of the electrode prepared in Example 1.
[0032] Figure 3 This is the XPS graph of the electrode prepared in Example 8. DETAILED DESCRIPTION
[0033] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.
[0034] In a first aspect of the present disclosure, a method for preparing a catalyst-loaded electrode is provided, the method comprising the following steps S1 to S3:
[0035] S1. Obtain an electrolyte containing metal ions, wherein the electrolyte further contains a polymer binder, the weight ratio of the metal ions to the polymer binder is (0.05-0.5):1, and the metal ions are calculated as a single metal;
[0036] S2, placing the working electrode in the electrolyte to perform an electrodeposition reaction to obtain a working electrode after the reaction;
[0037] S3, drying and calcining the working electrode after the reaction to obtain a catalyst-loaded electrode.
[0038] According to the present disclosure, in step S1, the metal ion may be a metal ion selected from group VIII, group IB, group VIB, and group VIIB. Further, the metal ion may be at least one selected from cobalt ions, nickel ions, iron ions, copper ions, and manganese ions. In a preferred embodiment, the metal ions are cobalt ions and nickel ions, wherein the molar ratio of the cobalt ions to the nickel ions may be (1 to 3): 1, and the catalyst prepared using cobalt ions and nickel ions has better economy than other precious metal catalysts, and is easy to control production costs.
[0039] The polymer binder can be at least one selected from quaternary ammonium salt polymers, quaternary phosphate polymers and quaternary sulfide polymers; the weight average molecular weight of the above polymers can be adjusted within a large range, specifically, the weight average molecular weight of the above polymers can be 5000 to 20000.
[0040] In a preferred embodiment, the polymer binder is at least one selected from polymethacryloyloxyethyl trimethyl ammonium chloride, polydimethyl diallyl ammonium chloride, quaternized polyvinyl imidazole and polyacrylamide propyl trimethyl ammonium chloride, and polymethacryloyloxyethyl trimethyl ammonium chloride is most preferred. Selecting the above polymer as the polymer binder is conducive to further improving the catalytic activity and stability of the electrode.
[0041] In a preferred embodiment, the weight ratio of the metal ion to the polymer binder is (0.08-0.45):1, and the metal ion is calculated as a single metal.
[0042] The concentration of the metal ions in the electrolyte can be adjusted in a wide range. Specifically, the concentration of the metal ions can be 10 to 100 mmol / L, preferably 30 to 80 mmol / L. The anions in the electrolyte can be various anions commonly found in the art, for example, Cl- Br - 、NO3 - 、SO4 - The electrolyte can be purchased commercially or prepared in a laboratory, for example, a suitable amount of metal salt is dissolved in deionized water, and the polymer binder is added in proportion to obtain the electrolyte.
[0043] According to the present disclosure, in step S2, the metal oxide can be electrochemically deposited from the electrolyte on the surface of the working electrode through the electrodeposition reaction to obtain an electrode loaded with a catalyst precursor (ie, the working electrode after the reaction).
[0044] In a preferred embodiment, the method further includes: pre-treating the working electrode before performing the electrodeposition reaction to remove impurities on the surface of the working electrode and further improve the catalytic stability of the electrode. The pre-treatment may include: soaking and ultrasonic cleaning the working electrode with an inorganic acid and / or an organic solvent. Specifically, the inorganic acid may be diluted hydrochloric acid, which can effectively remove oxides on the surface of the working electrode; the organic solvent may be acetone, which can remove oil stains on the surface of the working electrode. The pre-treatment may further include the process of rinsing the residual reagent on the working electrode with deionized water and drying it. The drying method may be natural air drying at room temperature or vacuum drying.
[0045] In a preferred embodiment, the electrodeposition reaction includes a first reaction stage, a second reaction stage and a third reaction stage performed sequentially; wherein the conditions of the first reaction stage include: a current density of -1 mA / cm 2 To -1.5mA / cm 2 , time is 60 to 120 s; the conditions of the second reaction stage include: current density is -0.2 mA / cm 2 To -0.5mA / cm 2 , time is 10 to 30 minutes; the conditions of the third reaction stage include: current density is -0.052mA / cm 2 To -0.1mA / cm 2 , the time is 60 to 90 minutes. After each reaction stage, the working electrode can be taken out and repeatedly cleaned with a cleaning agent (such as deionized water and ethanol) for several times, and then dried (drying temperature is, for example, 80 to 100°C) before proceeding to the next reaction stage. The three-stage electrodeposition reaction is used to prepare the catalyst, and a uniformly loaded metal oxide catalyst can be gradually formed on the surface of the working electrode. Compared with the conventional one-stage electrodeposition process, it can promote a closer combination of the catalyst and the electrode substrate, and is not easy to fall off, so that the catalytic activity and stability are higher.
[0046] The electrodeposition reaction can be carried out using a conventional electrode system in the art. For example, the electrodeposition reaction can be carried out using a three-electrode system, which includes a reference electrode, a counter electrode and the working electrode. The working electrode can be at least one selected from a nickel foam sheet electrode, a corrugated carbon electrode, a metal platinum electrode and a carbon paper electrode, preferably a nickel foam sheet electrode; further, the nickel foam sheet can have a thickness of 100 to 500 μm, and an area of preferably 0.5 to 2 cm 2 ; The reference electrode can be a silver / silver chloride electrode and / or a saturated calomel electrode; the counter electrode can be a platinum sheet electrode and / or a carbon rod electrode.
[0047] According to the present disclosure, in step S3, the drying conditions may include: a temperature of 80 to 100°C and a time of 12 to 24 hours. The calcination conditions may include: a temperature of 200 to 400°C, a heating rate of 1 to 5°C / min, and a time of 1.5 to 3 hours. Preferably, the calcination atmosphere is an inert gas, such as nitrogen, argon, helium, etc., preferably argon. By calcining in an inert atmosphere, the obtained catalyst can be enriched with oxygen vacancies, so that the catalyst can effectively enhance the adsorption of nitrate when used in the electrocatalytic nitrate reduction reaction, thereby improving the catalytic reaction activity and conductivity. The calcination can be carried out using calcination equipment commonly used in the art, such as a tubular furnace, and the temperature can be naturally lowered to room temperature after the calcination is completed.
[0048] In a second aspect of the present disclosure, a catalyst-loaded electrode prepared by the method described in the first aspect of the present disclosure is provided. The catalyst is a spinel metal oxide catalyst, and the catalyst loading amount can be 0.5 to 6 mg / cm 2 The electrode has good electrical conductivity and is particularly suitable for electrocatalytic production of ammonia, showing excellent catalytic activity and stability.
[0049] In a third aspect of the present disclosure, there is provided a use of the catalyst-loaded electrode described in the second aspect of the present disclosure in electrocatalytic production of ammonia.
[0050] Specifically, the application may include: when applying a potential of -0.2V to -0.8V ((relative to reversible hydrogen electrode, vs. RHE), using the electrode as a working electrode, and performing a nitrate reduction reaction in an electrolyte solution containing nitrate. Further, the electrolyte solution may be a solution containing 0.1-0.5 mol / L sodium hydroxide or potassium hydroxide, and 0.1-0.5 mol / L sodium nitrate or potassium nitrate. The catalyst-loaded electrode is used for the reaction, and a Faraday efficiency of more than 92% and a reaction efficiency of more than 1500 μmol·h -1 cm -2 The NH3 yield and high stability under 20h continuous electrolysis.
[0051] The present invention adds a polymer adhesive to the electrolyte and adopts an electrodeposition method to prepare a catalyst-loaded electrode. The catalyst is more tightly combined with the electrode matrix and is not easy to fall off. The catalytic activity and stability are high, and the preparation operation is simple, and the requirements for equipment are low. It has a broad market application prospect. The catalyst-loaded electrode is applied to the electrocatalytic nitrate reduction reaction to synthesize ammonia, which opens a way for the design and preparation of nitrate reduction catalysts for ammonia production in the future, and has great application value in wastewater treatment, ammonia industrial product synthesis, etc.
[0052] The present disclosure is further illustrated by the following examples.
[0053] In the following examples, unless otherwise specified, all reagents used are commercially available chemical reagents and there are no particular limitations thereto.
[0054] The lattice structure of the catalyst loaded on the surface of the electrode prepared in the embodiment was detected by X-ray diffraction (XRD). The test conditions were: range 5°~70°, scanning speed 5°min -1 .
[0055] X-ray photoelectron spectroscopy (XPS) was used to detect the oxygen vacancies of the catalyst loaded on the surface of the electrode prepared in the embodiment. The test conditions were: the excitation source used in the experiment was monochromatic Al K α X-ray, power is about 150W, X-ray spot area is 500μm. The basic vacuum of the spectrometer is 2×10 -10 mbar, with the neutralizing gun turned on during the test.
[0056] Catalyst loading of electrode = (m-m0) / S,
[0057] Wherein, m0 represents the electrode weight before the reaction (i.e., the electrode weight without catalyst loading), m represents the electrode weight after the reaction (i.e., the electrode weight with catalyst loading), and S represents the electrode area of the catalyst loading portion.
[0058] Example 1
[0059] (1) Take a 200 μm thick nickel foam sheet and cut it into a 1×2 cm rectangle. Use acetone and 6 mol / L hydrochloric acid solution to ultrasonically clean it for 15 min each. Then rinse the surface of the nickel foam sheet repeatedly with deionized water and ultrasonically clean it in deionized water for 15 min. Finally, dry it at room temperature for later use.
[0060] (2) Weigh 1.455 g Co(NO3)2·6H2O and 0.727 g Ni(NO3)2·6H2O, add to 100 mL deionized water, and continue stirring for 20 min until the solid is completely dissolved to obtain a mixed solution. Add 1.0 g polymethacryloyloxyethyl trimethylammonium chloride to the above solution, and ultrasonicate for 30 min until the solid is completely dissolved to obtain an electrolyte. In this electrolyte, Co 2+ with Ni 2+ The molar ratio of Co is 2:1. 2+ The concentration is 50mmol / L, Ni 2+ The concentration is 25mmol / L, Co 2+ with Ni 2+ The weight ratio of the total amount of polymethacryloyloxyethyltrimethylammonium chloride is 0.44:1.
[0061] (3) Conducting an electrochemical deposition reaction in the above-prepared electrolyte, using a three-electrode system during the reaction, wherein the working electrode is the nickel foam sheet pretreated in step (1), the reference electrode is a silver / silver chloride electrode, and the counter electrode is a platinum sheet, in the following order:
[0062] First reaction stage: at -1mA / cm 2 The reaction was carried out for 60s at the current density.
[0063] Second reaction stage: at -0.4mA / cm 2 The reaction was carried out for 10 min at the current density.
[0064] The third reaction stage: at -0.1mA / cm 2 The reaction was carried out for 60 min at the current density.
[0065] After each reaction stage, the nickel foam sheet was taken out, washed repeatedly with deionized water and ethanol for several times, and then placed in an oven at 100° C. for drying, and finally a nickel foam sheet loaded with a catalyst precursor was obtained.
[0066] (4) In an argon atmosphere, the nickel foam sheet loaded with the catalyst precursor was placed in a tube furnace for calcination, and the heating rate was controlled to be 1°C / min, and the temperature was raised to 300°C, maintained for 3 hours, and then cooled naturally to obtain the nickel foam sheet electrode loaded with NiCo2O4 catalyst prepared in this embodiment. The catalyst loading of the electrode was 5±0.5 mg / cm 2 , XRD spectrum as Figure 1 , XPS spectrum as Figure 2 , it can be seen that the NiCo2O4 catalyst is rich in oxygen vacancies.
[0067] Example 2
[0068] The catalyst-loaded electrode was prepared according to the method of Example 1, except that in step (2), polydimethyldiallyl ammonium chloride was used as the polymer binder instead of polymethacryloyloxyethyltrimethylammonium chloride, Co 2+ with Ni 2+ The weight ratio of the total amount of polydimethyldiallylammonium chloride is 0.44:1.
[0069] The catalyst loading of the electrode was 4.5 ± 0.4 mg / cm 2 The NiCo2O4 catalyst is rich in oxygen vacancies, and its XRD spectrum is similar to Figure 1 similar.
[0070] Example 3
[0071] The catalyst-loaded electrode was prepared according to the method of Example 1, except that in step (2), quaternary ammonium polyvinyl imidazole was used as the polymer binder instead of polymethacryloyloxyethyl trimethyl ammonium chloride, Co 2+ with Ni 2+ The weight ratio of the total amount of polyvinyl imidazole to quaternary ammonium polyvinyl imidazole is 0.44:1.
[0072] The catalyst loading of the electrode was 4.8 ± 0.5 mg / cm 2 The NiCo2O4 catalyst is rich in oxygen vacancies, and its XRD spectrum is similar to Figure 1 similar.
[0073] Example 4
[0074] The catalyst-loaded electrode was prepared according to the method of Example 1, except that in step (2), Co 2+ with Ni 2+ The weight ratio of the total amount of polymethacryloyloxyethyltrimethylammonium chloride is 0.05:1.
[0075] The catalyst loading of the electrode was 4.6 ± 0.3 mg / cm 2 The NiCo2O4 catalyst is rich in oxygen vacancies, and its XRD spectrum is similar to Figure 1 similar.
[0076] Example 5
[0077] The catalyst-loaded electrode was prepared according to the method of Example 1, except that in step (2), Co 2+ with Ni 2+ The weight ratio of the total amount of polymethacryloyloxyethyltrimethylammonium chloride is 0.5:1.
[0078] The catalyst loading of the electrode was 4.0 ± 0.6 mg / cm 2 The NiCo2O4 catalyst is rich in oxygen vacancies, and its XRD spectrum is similar to Figure 1 similar.
[0079] Example 6
[0080] Weigh 1.455 g Co(NO3)2·6H2O and 0.727 g Cu(NO3)2·6H2O and add them to 100 mL deionized water. 2+ With Cu 2+ The molar ratio of Co is 2:1. 2+ The concentration is 50mmol / L, Cu 2+ The concentration is 25mmol / L.
[0081] The catalyst loading of the electrode was 4.7 ± 0.6 mg / cm 2 The CuCo2O4 catalyst is rich in oxygen vacancies, and its XRD spectrum is similar to Figure 1 similar.
[0082] Example 7
[0083] The catalyst-loaded electrode was prepared according to the method of Example 1, except that in step (3), the electrochemical deposition reaction did not undergo three reaction stages, but only at -1 mA / cm 2 The reaction was carried out for 10 min at the current density.
[0084] The catalyst loading of the electrode was 3.0 ± 0.4 mg / cm 2 The NiCo2O4 catalyst is rich in oxygen vacancies, and its XRD spectrum is similar to Figure 1 similar.
[0085] Example 8
[0086] The catalyst-loaded electrode was prepared according to the method of Example 1, except that in step (4), the calcination atmosphere was air.
[0087] The catalyst loading of the electrode is 5±0.5 mg / cm 2 , XPS spectrum as Figure 3 , indicating that the NiCo2O4 catalyst contains fewer oxygen vacancies. The XRD spectrum is similar to Figure 1 Similarly, it shows that the calcination atmosphere will not affect the lattice structure of NiCo2O4 catalyst.
[0088] Comparative Example 1
[0089] The catalyst-loaded electrode was prepared according to the method of Example 1, except that in step (2), the electrolyte did not contain polymethacryloyloxyethyltrimethylammonium chloride.
[0090] Test Example
[0091] The electrodes prepared in the examples and comparative examples were used to electrocatalyze nitrate reduction to synthesize ammonia. The examples were used as test samples and the comparative examples were used as control samples to detect their catalytic activity and stability in the electrocatalytic nitrate reduction to synthesize ammonia reaction.
[0092] The nitrate electroreduction experiment was carried out in a double-chamber H-type electrolytic cell separated by a cation exchange membrane (Nafion 117), which used a three-electrode system connected to an electrochemical workstation for measurement. Mercury / mercury oxide electrode and platinum sheet electrode were used as reference electrode and counter electrode, respectively, catalyst-loaded nickel foam sheet was used as working electrode, and 0.1 mol / L sodium hydroxide and 0.1 mol / L sodium nitrate aqueous solution were used as electrolyte. All potentials in the test were converted to reversible hydrogen electrode (RHE) as a reference scale. After the reaction was completed, the Nessler reagent method was used to detect the ammonia production and calculate the Faraday efficiency and yield.
[0093] The calculation method of NH3 Faradaic efficiency and NH3 yield involved in the experiment is as follows:
[0094] FE NH3 =(n×V×C NH3 ×F) / (M NH3 ×Q)×100%
[0095] NH3 yield = (V × C NH3 ) / (A×t)
[0096] Where n is the number of electrons required to transfer to generate one NH3 molecule in the reaction (n = 8 in this reaction), V is the volume of the electrolyte (in L), C NH3 is the concentration of NH3 generated (in mg / L), F is the Faraday constant (F=96485C / mol), M NH3 is the relative molecular mass of NH3 (17 g / mol), Q is the charge of the electrolytic reaction (in C), t is the time of the electrolytic reaction (in h), S is the area of the working electrode (in cm 2 ).
[0097] Test parameters: The voltage was set to -0.4V (relative to the reversible hydrogen electrode, vs. RHE), the test time for each cycle was 2h, and the electrolyte in the cathode chamber was stirred at a speed of 300 rpm. The stability test was carried out for 10 cycles, each cycle was 2h, and the NH3 Faraday efficiency and yield in the cycle were tested after each cycle. At the same time, a new electrolyte was replaced and the next cycle test was carried out using the same working electrode. The test results are shown in Tables 1 and 2.
[0098] As can be seen from Tables 1 and 2, in the 10 cycles (20 h) of the reaction, the comparative example 1 showed a significant decrease in the catalytic activity of catalyzing the reduction of nitrate to ammonia, and black catalyst powder was found to fall off at the bottom of the electrolytic cell. The catalysts prepared in Examples 1 to 8 showed high stability in terms of NH3 Faraday efficiency and NH3 yield, and no catalyst shedding occurred.
[0099] Table 1
[0100]
[0101] Table 2
[0102]
[0103]
[0104] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0105] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0106] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing a catalyst-loaded electrode, characterized in that: The method comprises the following steps: Obtaining an electrolyte containing metal ions, wherein the electrolyte further contains a polymer binder, and the weight ratio of the metal ions to the polymer binder is (0.05-0.5):1; Placing the working electrode in the electrolyte to perform an electrodeposition reaction to obtain a working electrode after the reaction; The working electrode after the reaction is dried and calcined to obtain a catalyst-loaded electrode.
2. The method according to claim 1, wherein: The metal ion is at least one selected from cobalt ion, nickel ion, iron ion, copper ion and manganese ion; Preferably, the metal ions are cobalt ions and nickel ions, wherein the molar ratio of the cobalt ions to the nickel ions is (1-3):
1.
3. The method according to claim 1, wherein: The polymer binder is at least one selected from quaternary ammonium salt polymers, quaternary phosphate salt polymers and quaternary sulfide salt polymers; Preferably, the polymer binder is at least one selected from polymethacryloyloxyethyltrimethylammonium chloride, polydimethyldiallylammonium chloride, quaternized polyvinylimidazole and polyacrylamidepropyltrimethylammonium chloride.
4. The method according to claim 1, wherein: In the electrolyte, the concentration of the metal ions is 10 to 100 mmol / L.
5. The method according to claim 1, wherein: The electrodeposition reaction comprises a first reaction stage, a second reaction stage and a third reaction stage which are performed sequentially; The conditions of the first reaction stage include: a current density of -1 mA / cm 2 To -1.5mA / cm 2 , time is 60~120s; The conditions of the second reaction stage include: a current density of -0.2 mA / cm 2 To -0.5mA / cm 2 , time is 10 to 30 minutes; The conditions of the third reaction stage include: a current density of -0.052 mA / cm 2 To -0.1mA / cm 2 , time is 60 to 90 minutes.
6. The method according to claim 1 or 5, wherein: The electrodeposition reaction is carried out using a three-electrode system, which includes a reference electrode, a counter electrode and the working electrode; The working electrode is at least one selected from a nickel foam electrode, a carbon electrode, a metal platinum electrode and a carbon paper electrode; The reference electrode is a silver / silver chloride electrode and / or a saturated calomel electrode; The counter electrode is a platinum sheet electrode and / or a carbon rod electrode.
7. The method according to claim 1, wherein: The drying conditions include: a temperature of 80 to 100° C. and a time of 12 to 24 hours.
8. The method according to claim 1, wherein: The calcination conditions include: the calcination atmosphere is an inert gas, the temperature is 200 to 400° C., and the time is 1.5 to 3 hours.
9. A catalyst-loaded electrode prepared by the method according to any one of claims 1 to 8.
10. Use of the catalyst-loaded electrode according to claim 9 in electrocatalytic production of ammonia.